2021
DOI: 10.1111/epi.16979
|View full text |Cite
|
Sign up to set email alerts
|

Gut metabolite S‐equol ameliorates hyperexcitability in entorhinal cortex neurons following Theiler murine encephalomyelitis virus‐induced acute seizures

Abstract: Objective A growing body of evidence indicates a potential role for the gut–brain axis as a novel therapeutic target in treating seizures. The present study sought to characterize the gut microbiome in Theiler murine encephalomyelitis virus (TMEV)‐induced seizures, and to evaluate the effect of microbial metabolite S‐equol on neuronal physiology as well as TMEV‐induced neuronal hyperexcitability ex vivo. Methods We infected C57BL/6J mice with TMEV and monitored the development of acute behavioral seizures 0–7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In recent years, there has been an increasing interest in the research field of neurogastroenterology. Evidence from human and animal cases suggests that specific changes in the intestinal flora cause neurodegenerative diseases, modify host behaviour and seizure semiology [13][14][15][16][17]. A bidirectional crosstalk between the intestinal flora and the brain is mediated via the microbiome-gutbrain axis [18] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in the research field of neurogastroenterology. Evidence from human and animal cases suggests that specific changes in the intestinal flora cause neurodegenerative diseases, modify host behaviour and seizure semiology [13][14][15][16][17]. A bidirectional crosstalk between the intestinal flora and the brain is mediated via the microbiome-gutbrain axis [18] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Allobaculum is a mouse commensal and associated with 5-hydroxytryptamine levels and short-chain fatty acid production ( Wu et al., 2020 ; Wang et al., 2020 ; Li et al., 2020 ). Several lines of studies have found that the reduction of genus Allobaculum is involved in behavior deficits and neurological disease ( Davis et al., 2017 ; Gubert et al., 2020 ; Xie et al., 2020 ; Gallucci et al., 2021 ). Correlation analysis found a positive association between decreased genus Allobaculum and decreased social deficits in BTBR mice.…”
Section: Discussionmentioning
confidence: 99%
“…The attention has been mainly focused on dietary modification, microbiome supplementations, or manipulation of gut microbiota from mouse models, to evaluate pathological outcomes such as a reduction in seizures' frequency 16 . On the other hand, the number of studies demonstrating a link between gut microbiota alterations and increased neuronal excitability and seizures is constantly increasing, shedding light on the potential mechanisms, pharmacological targets, and treatments 31–34 . It is worth noting that literature studies can be divided into those demonstrating a direct or an indirect impact of microbiota manipulation on epilepsy features.…”
Section: The Mgb Axis and Epilepsymentioning
confidence: 99%
“…16 On the other hand, the number of studies demonstrating a link between gut microbiota alterations and increased neuronal excitability and seizures is constantly increasing, shedding light on the potential mechanisms, pharmacological targets, and treatments. [31][32][33][34] It is worth noting that literature studies can be divided into those demonstrating a direct or an indirect impact of microbiota manipulation on epilepsy features. Among those included in the first group, some studies reported an increased susceptibility to seizures that could be transferred by fecal microbiota transplantation as well as this latter can confer seizure protection and even be used to identify molecules (microbiota metabolites) as potential treatments.…”
Section: Preclinical Datamentioning
confidence: 99%